Inferioritas dan Superioritas Tokoh-tokoh dalam Novel Selena Karya Tere Liye (Kajian Psikologi Sastra Alferd Adler): Inferiority and Superiority of Characters in The Novel Selena by Tereliye (A Study Of Alferd Adler’s Literary Psychology) - Mawardy, Shintya; Meliasanti, Ferina; Damanhuri, Damanhuri (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
The purpose of this study is to describe the forms of inferiority and superiority found in the novel Selena by Tere Liye. The benefits of this study are to increase knowledge about literary science, especially in the field of literary psychology research. This study uses a qualitative approach with a descriptive research method. The data used in this study are sentences, quotes, or excerpts that show conformity with Alfred Adler's Inferiority and Superiority theory. The data collection techniques used in this study are library techniques, reading techniques, and note-taking techniques. Then the data analysis technique in this study uses the Miles and Huberman analysis technique which consists of data collection, data reduction, data display, and drawing conclusions from the data obtained. The results of this study indicate the existence of forms of inferiority in the form of timidity, hesitance, insecurity, cowardice, and submissive obedience. Meanwhile, the form of superiority contained in the Selena novel by Tere Liye is in the form of the final goal that the main character wants to achieve, namely to become a student at the High Shadow Academy (ABTT) and to be able to defend himself to become a student at the High Shadow Academy (ABTT), then the strength of struggle as a form of compensation manifested in the form of courage, stubbornness, rebelliousness, and opposition. And the struggle that is carried out is to achieve personal superiority.